Real-Time Challenging of ERα Y537S Mutant Transcriptional Activity in Living Cells - Manuela Cipolletti; Sara Pescatori; Filippo Acconcia (Endocrines, 2021)
Metastatic estrogen receptor α (ERα)-expressing breast cancer (BC) occurs after prolonged patient treatment with endocrine therapy (ET) (e.g., aromatase inhibitors—AI; 4OH-tamoxifen—4OH-Tam). Often these metastatic BCs express a mutated ERα variant (e.g., Y537S), which is transcriptionally hyperactive, sustains uncontrolled proliferation, and renders tumor cells insensitive to ET drugs. Therefore, new molecules blocking hyperactive Y537S ERα mutation transcriptional activity are requested. Here we generated an MCF-7 cell line expressing the Y537S ERα mutation stably expressing an estrogen-responsive element (ERE) promoter, which activity can be monitored in living cells. Characterization of this cell line shows both hyperactive basal transcriptional activity with respect to normal MCF-7 cells, which stably express the same ERE-based promoter and a decreased effect of selective ER downregulators (SERDs) in reducing Y537S ERα mutant transcriptional activity with respect to wild type ERα transcriptional activity. Kinetic profiles of Y537S ERα mutant-based transcription produced by both drugs inducing receptor degradation and siRNA-mediated depletion of specific proteins (e.g., FOXA1 and caveolin1) reveals biphasic dynamics of the inhibition of the receptor-regulated transcriptional effects. Overall, we report a new model where to study the behavior of the Y537S ERα mutant that can be used for the identification of new targets and pathways regulating the Y537S ERα transcriptional activity.